Tetramethylpyrazine alleviates acute pancreatitis inflammation by inhibiting pyroptosis via the NRF2 pathway - Li, Huangen; Gao, Yi; Huang, Minglian; Zhang, Hongling; Wu, Qingqing; Huang, Youpei; Ye, Xiaotong; Chen, Weiwen (Frontiers in Pharmacology, 2025)
ObjectiveTetramethylpyrazine (TMPZ), an active alkaloid derived from traditional Chinese medicine, has shown anti-inflammatory and anti-pyroptotic properties. However, its role in acute pancreatitis (AP)-induced pyroptosis remains unclear. This study aims to investigate the effects of TMPZ on AP-induced pyroptosis and its potential mechanisms.Materials and methodsA cerulein-induced AP rat model was used to evaluate TMPZ’s protective effects in vivo, and its mechanisms were explored using AR42J cells in vitro. Pancreatic injury was assessed by hematoxylin-eosin staining, TUNEL assay, and serum biochemistry. Transmission electron microscopy, immunofluorescence, Western blotting, and quantitative real-time polymerase chain reaction (RT-qPCR) were conducted to examine pyroptosis and related signaling pathways. Cytotoxicity and apoptosis were measured by CCK-8, LDH assays, and Hoechst 33342/PI staining. The role of NRF2 in TMPZ’s effects was further evaluated using NRF2 siRNA.ResultsTMPZ alleviated pancreatic histopathological damage, reduced apoptosis, and decreased serum amylase levels and pro-inflammatory cytokines (IL-1β, IL-18). TMPZ also suppressed pyroptosis by inhibiting NLRP3 inflammasome activation and downregulating pyroptosis-related proteins (NLRP3,caspase-1, ASC, GSDMD) while upregulating NRF2 and HO-1 expression. NRF2 siRNA attenuated TMPZ’s anti-inflammatory and pyroptosis-inhibitory effects, confirming the involvement of the NRF2 pathway.ConclusionTMPZ mitigates AP-induced inflammation and injury by modulating pyroptosis via the NRF2 signaling pathway. These findings suggest TMPZ’s therapeutic potential for AP.